1993
DOI: 10.1159/000126393
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic versus Pituitary Stimulation of Luteinizing Hormone Secretion in the Prepubertal Female Lamb

Abstract: Glutamate and aspartate have been hypothesized to function as neurotransmitters in the regulation of the gonadotropin-releasing hormone (GnRH) neurosecretory system. We, therefore, determined if hypothalamic stimulation of luteinizing hormone (LH) secretion in the intact prepubertal female lamb could be achieved by intravenous injection of N-methyl-D,L-aspartate (NMA), a glutamate agonist. A pilot study determined a dose of NMA that would induce physiologic pulses of LH (GnRH). Subsequently, we compared the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A complementary hypothesis is that the increased LHRH secretion during the induction of breeding season also implicates stimulatory mechanisms. In support of this hypothesis, administration of N-methyl-D,L-aspartic acid (NMDA), an agonist of neuroexcitatory amino acid receptors, acutely stimulates LH secretion in seasonal species such as the hamster and the sheep [10][11][12][13][14][15]. However, this stimulatory effect is larger during periods of photoinhibited LH secretion than during photostimulated periods, suggesting that excitatory amino acids are involved in the photoperiodic regulation of LH secretion.…”
Section: Introductionmentioning
confidence: 99%
“…A complementary hypothesis is that the increased LHRH secretion during the induction of breeding season also implicates stimulatory mechanisms. In support of this hypothesis, administration of N-methyl-D,L-aspartic acid (NMDA), an agonist of neuroexcitatory amino acid receptors, acutely stimulates LH secretion in seasonal species such as the hamster and the sheep [10][11][12][13][14][15]. However, this stimulatory effect is larger during periods of photoinhibited LH secretion than during photostimulated periods, suggesting that excitatory amino acids are involved in the photoperiodic regulation of LH secretion.…”
Section: Introductionmentioning
confidence: 99%
“…NMDA stimulates release of LH and LHRH in adult rats and monkeys in vivo (Price et al, 1978, Olney et al, 1976;Brann and Mahesh, 1997;van den Pol et al, 1994;Bourguignon et al, 1995), and glutamate, NMDA, and kainate all stimulate LHRH/ LH release in sexually immature monkeys (Gay and Plant, 1987;Medhamurthy et al, 1990), rats (Bourguignon et al, 1989;Brann and Mahesh, 1992;Cicero et al, 1988), sheep (I'Anson et al, 1993), and fetal sheep (Bettendorf et al, 1999) in vitro and in vivo. Moreover, stimulation of NMDA receptors results in precocious puberty in rats and monkeys (Plant et al, 1989;Urbanski and Ojeda, 1990), whereas administration of the NMDA receptor blockers, MK-801 or 2-amino-5-phosphonovaleric acid (AP-5), delays the timing of puberty in rats (MeijiRoelofs et al, 1991;Urbanski and Ojeda, 1990;Wu et al, 1990;MacDonald and Wilkinson, 1990).…”
Section: The Pubertal Reduction In Gabaergic Inhibition Is Followed Bmentioning
confidence: 99%
“…fed lambs which suggested that the effect of feed restriction was on central mechanisms controlling LHRH release rather than on LHRH synthesis. It is further evident that N-methyl-D-aspartate activates the release of accumulated GnRH from the hypothalamus which is inhibited as a result of undernutrition (Ebling et al 1990;I'Anson et al 1990), suggesting that the central nervous system was responsible for the release of GnRH (Dunn & Moss, 1992). Since dietary protein:energy ratios influence intermediary metabolism leading to changes in the circulatory concentrations of insulin, certain amino acids and non-esterified fatty acids (Brockman & Laarveld, 1986;Howard et al 1987;Patil, 1993), it is proposed that these metabolites may act as nutritional signals influencing LH secretion.…”
Section: Possible Mechanisms Of Effects Of Protein Nutrition O N Reprmentioning
confidence: 99%